Genome Wide Identification of the MLO Gene Family Associated with Powdery Mildew Resistance in Rubber Trees (Hevea brasiliensis) - Liyanage, K.K.; Khan, S.; Herath, V.; Brooks, S.; Mortimer, P.E.; Nadir, S.; Hyde, Kevin D.; Xu, J.C. (Springer, 2020)
Powdery mildew (PM) is one of the most destructive diseases affecting rubber trees (Hevea brasiliensis), leading to severe yield losses. Sulfur dusting is used to control the propagation of the disease, and no specific fungicides have been developed yet. Therefore, identification of genetic level disease resistance in the rubber trees is very crucial. In this study, we describe the whole-genome sequencing of a PM resistant rubber clone, RRIC 52, as well as a PM susceptible clone, PB 235, using massively parallel paired-end sequencing. The MLO (mildew resistance locus O) genes were identified and analyzed for their structural features, and the variations were compared in the MLO gene family between the two clones. Sequencing results showed that RRIC 52 contained 4,280,477 SNPs and 400,667 InDels, while PB 235 contained 3,651,524 SNPs and 318,899 InDels. We identified 34 MLO genes (HbMLO 1 to 34) in the rubber genome. Multiple sequence alignment identified the conserved MLO domain and its TM domain in all HbMLO proteins. Sequence analysis identified non-synonymous variations (NSVs) in 12 HbMLO proteins. Phylogenetic analysis of the HBMLO genes revealed seven different clades. Six HbMLO genes in Clade V were orthologous to Arabidopsis genes where PM interaction was previously identified. The outcomes of this study widen the understanding of the MLO gene family, which can be used in breeding disease resistant rubber varieties in the future.